Gas-phase Oxygenation and Sulfurization Processes of Fullerene Cations - Nian Zhao; Xiaoyi Hu; Yanan Ge; Congcong Zhang; Aigen Li; Junfeng Zhen; Xuejuan Yang (The Astrophysical Journal)
Atomic oxygen and sulfur are known to efficiently react with fullerenes and may thus form a long list of oxygenated and sulfurated fullerene species in the interstellar medium (ISM). In this work, the gas-phase collision reactions between fullerene (C _60 and C _54/56/58 ) cations and ^18 O or S atoms are investigated. Oxygenated and sulfurated fullerene cations ([C _60 ^18 O _1−6 ] ^+ , [C _54/56/58 ^18 O _1−3 ] ^+ and [C _60 S _1−4 ] ^+ , [C _54/56/58 S _1−4 ] ^+ ) are efficiently formed. Under laser irradiation, O-atom and CO-unit loss channels are identified in the photodeoxygenation processes; [C _60 O] ^+ only has an O-atom loss channel. Smaller fullerene cations can be produced through sequential steps, and species with repeatedly lost CO units, i.e., fullerenes containing odd carbon numbers (e.g., 55 or 57 C atoms), can be produced in the photodeoxygenation processes of oxygenated fullerene cations. A S-atom loss channel and no CS-unit loss channel are identified in the photodesulfurization processes. Through theoretical calculations, the structures of oxygenated and sulfurated fullerene cations (e.g., [C _60 ^18 O] ^+ and [C _60 S] ^+ ) and the bonding energies for the formation reaction pathways are investigated, together with their IR spectra. The exothermic energy for each reaction pathway is relatively high. Consequently, the oxygenation or sulfurization states and forms of fullerene compounds are intricate and complex. In addition, different types of oxygenation and sulfurization bonds are obtained with their evolution. Importantly, we infer that the photodeoxygenation of mono-oxygenated fullerene species or the photodesulfurization of sulfurated fullerene species is not involved in the top-down chemical evolution routes of buckminsterfullerene (C _60 ) in the ISM.